Analgesic effect of epidural maropitant and the combination of maropitant and lidocaine in cats subjected to ovariohysterectomy (Research, Society and Development, 2022)
The present study aimed to evaluate the efficacy of epidural maropitant administered with or without lidocaine for post-operative analgesia in cats. Forty cats submitted to epidural administration of treatments followed by ovariohysterectomy were assessed in this study. The cats were randomly distributed into experimental groups: epidural control group (ECG), which received saline; epidural lidocaine group (ELG), which received 3 mg/kg of 2% lidocaine without vasoconstrictor; epidural maropitant group (EMG), which received 1 mg/kg of maropitant; and epidural lidocaine and maropitant group (ELMG), which received 3 mg/kg of 2% lidocaine without vasoconstrictor and 1 mg/kg of maropitant. In all groups, sacrococcygeal epidural administration was performed. Physiological variables were measured during the surgical procedure. Post-operative pain was assessed over six hours by using a visual analogue scale and a multidimensional scale for assessment of post-operative pain in cats. During the surgical procedure, the heart rate in the ELMG was lower than that in the EMG. The ECG required a higher quantity of rescue analgesia in the post-operative period. The EMG and ELMG showed lower pain scores than the ECG. Epidural administration of lidocaine and maropitant, alone or in combination, provided similar analgesic effects in the post-operative period. Although the results indicate analgesic effects of lidocaine and maropitant used alone for two hours and the combination for three hours, the clinical use is limited because the duration of analgesia is too short for postoperative analgesia.